Resection of Sentinel Lymph Nodes by an Extraperitoneal Minilaparoscopic Approach Using Indocyanine Green for Uterine Malignancies: A Preclinical Comparative Study. (August 2016) - Ferreira, Hélder; Nogueira-Silva, Cristina; Miranda, Alice; Correia-Pinto, Jorge
Background . The sentinel lymph node (SLN) concept might minimize surgical aggressiveness in cervical and endometrial malignancies. The aim of the study was to test the feasibility and reliability of minilaparoscopic extraperitoneal SLN excision after indocyanine green (ICG) cervical injection using a high-definition near infrared (NIR) imaging system in an in vivo porcine model. The same procedure was performed using conventional laparoscopic instruments and both outcomes were compared. Methods . Twenty-four animals were equally and randomly divided into a minilaparoscopic group (group A) and a 5-mm conventional laparoscopic group (group B). A high-definition NIR imaging system and a 30° ICG endoscope were used. First, ICG (0.5 mL) was injected in the paracervical region. The SLN coloring time was recorded. An extraperitoneal approach to the SLN was executed with the same CO2 retropneumoperitoneum pressures (10 mm Hg). In both groups, the times for SLN localization and excision, as well as complications, were registered. Finally, a laparotomy was then done to evaluate whether any stained SLN still remained. The same surgical team performed all experiments. Results . SLNs were identified and extraperitoneally excised in all animals without major complications. The SLN localization varied between animals from external iliac to preaortic regions. The surgical times were shorter with minilaparoscopy (39.3 ± 13 minutes) than with conventional 5-mm instruments (51.3 ± 14.17 minutes; P = .042). In group B, one stained SLN remained and was only detected by laparotomy. Conclusions . We confirmed the feasibility and reliability of extraperitoneal minilaparoscopic approach for identification, dissection, and excision of SLN using an NIR imaging system and ICG.